Evolving Service Innovation for The Late-mover Industry: The Case of Islamic Banking - Pertiwi, Ruspita Rani (Journal of Business Management and Islamic Banking, 2023)
Research Aims: This paper examines how Islamic banking in Indonesia, as a late-mover industry, evolves service innovation to attract customers and compete with already established conventional banking.  Design/methodology/approach: This qualitative research examines Indonesian Islamic Banking as a case study. This study involves two stages: investigating the case in-depth, detail, and context analysis using secondary data from various sources and in-depth interviews with stakeholders. Triangulation was employed to validate the entire result using various methods and data source triangulation. Research Findings: This research reveals that the development of service innovation in late movers is influenced by the sort of industry, the goals and values of the new industry's establishment, the resources owned, and market characteristics. While the dimensions of service innovation developed by late movers typically focus on new value systems, they emphasise value; meanwhile, in terms of technical or working models of the innovation, they tend to replicate or modify from first movers.